FINANCIAL AND ACCOUNTING ADMINISTRATION IN THE FEDERAL GOVERNMENT. - Bordner, H. W. (The Accounting Review, 1949)
In order to have good financial and accounting administration in a Government department or bureau, or in a business enterprise, we need to concern ourselves with certain fundamentals like a good general conception of the role of financial and accounting administration in the entire management of the unit. There must be a will on the part of the entire management to use accounting tools purposes. There must be a good organizational plan, both for the entire unit and for the accounting department. There has been a failure in public administration circles to recognize the role of accounting in public administration. The whole field of accounting is one of the last management areas to be developed. Accountants bear a fair share of the blame for this lag. It is believed that public administration is quite a way behind business in the development of the conception of the role of accounting in management control. It seems that there may be two reasons for such a lag in the Government sector: (1) There has been no overwhelming, compulsive urge in Government, such as exists in competitive business, for economical administration with intention to control of costs; and (2) the patterns of public administration in the Federal Government are fixed very strongly by tradition and the straight-jacket of statute.